2007
DOI: 10.1097/01.ede.0000276837.62405.bb
|View full text |Cite
|
Sign up to set email alerts
|

Hair Manganese and Hyperactive Behaviors: Pilot Study of School-Age Children Exposed Through Tap Water

Abstract: BACKGROUND:Neurotoxic effects are known to occur with inhalation of manganese particulates, but very few data are available on exposure to Mn in water. We undertook a pilot study in a community in Québec (Canada) where naturally occurring high Mn levels were present in the public water system. Our objective was to test the hypothesis that greater exposure to Mn via drinking water would be reflected in higher Mn content in hair which, in turn, would be associated with increased level of hyperactive behaviors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
39
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 23 publications
1
39
0
Order By: Relevance
“…The cytotoxic effects of Mn 2+ result in the development of manganism, a Parkinson-like neurodegeneration syndrome, in adults and cognitive and behavioral defects in children (12)(13)(14). Thus, identifying mechanisms that reduce cytosolic Mn 2+ levels during elevated exposure is of high clinical significance.…”
mentioning
confidence: 99%
“…The cytotoxic effects of Mn 2+ result in the development of manganism, a Parkinson-like neurodegeneration syndrome, in adults and cognitive and behavioral defects in children (12)(13)(14). Thus, identifying mechanisms that reduce cytosolic Mn 2+ levels during elevated exposure is of high clinical significance.…”
mentioning
confidence: 99%
“…A case-control study by Farias et al [63] found that chil dren with ADHD of both the inattentive and ADHDcombined types had higher serum manganese levels com pared with the controls, however the study did not control for potential confounders. Also, the study performed in Quebec reported a significant association between higher manganese levels in hair and drinking water and hyperactive behaviors in school children after controlling for sex, age and income [59].…”
Section: Manganese and Adhd Or Adhd-related Symptomsmentioning
confidence: 95%
“…Manganese (Mn) is a naturally occurring element that constitutes approximately 0.1% of the Earth's crust, and low levels of Mn in water, food, and air are ubiquitous [59]. Several authors have hypothesized that excessive amount of Mn could have detrimental effects on children's behavior patterns [59].…”
Section: Manganese and Adhd Or Adhd-related Symptomsmentioning
confidence: 99%
See 2 more Smart Citations